Aplikasi Shrinking Core Model Pada Sintesis Hidroksiapatit Dari Kulit Kerang Darah (Anadara Granosa) Dengan Menggunakan Metode Hidrotermal Suhu Rendah - Ervina Ervina; Ahmad Fadli; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite (HA) is a ceramic material that can be used as bone and dental implants. Hydroxyapatite can be synthesized from the cockle shell (Anadara granosa). The purpose of this study was to determine the effect of time and stirring rate on the characteristics of HA using a low temperature hydrothermal method as well as decide of the kinetics model with the approach of shrinking core models. There are 3 models that are used, namely diffusion through the liquid film control, diffusion through the layer results (HA) control, and chemical reaction control. Research procedures initiated by the reaction of 36.9 g NH4H2PO4 dissolved in 600 mL of water were then added as much as 39.37 g CaO at stirring rate of 100 rpm, 200 rpm, 300 rpm and reaction time of 5 minutes to 150 minutes. The mixture was reacted at a temperature of 90˚C to form a paste. The paste was dried in an oven at 120˚C for 12 hours and calcined at a temperature of 900˚C for 1 hour. The results showed that the product formed is 95% fraction massa of HA. Kinetics model that describes the events of the synthesis of HA for belong to model 2, i.e diffusion through the layer results (HA) control with the smallest error percentage of 16.15 % with the formula:Keywords: cockle shell, hydrothermal, hydroxiapatite, kinetics model, shrinking core model